Profil Pasien COVID-19 dengan Hipertensi di RS Lapangan Indrapura Surabaya - Muchammad Alydrus; Erwin Astha Triyono; Wardah Rahmatul Islamiyah (Malahayati Nursing Journal, 2026)
ABSTRACT Coronavirus Disease 2019 (COVID-19) is a type of disease caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2).  Hypertension is one of the comorbidities that can exacerbate COVID-19 in patients. This study aims to determine the profile of patient with COVID-19 and hypertension to support appropriate clinical management for these patients can be determined. A retrospective study was conducted to review the medical records of COVID-19 patients with hypertension who were treated at Indrapura Field Hospital in Surabaya during February - August 2021. Of the 3997 COVID-19 patients treated at the Indrapura Field Hospital, Surabaya for the period February - August 2021 the final sample obtained was 575 COVID-19 patients with hypertension (14,39%).  Two hundred and twenty-three (38,8%) were female patients and 352 (61,2%) were male patients.  The mean age is 47.2 years.  Most of the patients (209, 36,3%) were aged 41-50. The most common nutritional status in patients was Obesity I, found in 225 patients (39,1%).  Three hundred and sixty-one patients (62,8%) were self-employed.  COVID-19 patients with hypertension were classified as mild in 394 (68,5%). From all COVID-19 patients with hypertension, 540 recovered from their disease (93,3%).  The most frequently found clinical symptom was cough in 248 patients (43,1%) and vitamins were the most symptomatic therapy given to 572 patients (99,5%).  Type I hypertension was found in the most in patients, namely 258 patients (44,9%) and 426 patients received therapy, namely monotherapy (74,1%).  Another comorbidity that was found the most in patients COVID-19 with hypertension was diabetes (48, 8,3%).Conclusion: Of the 3997 COVID-19 patients who were treated at RS Lapangan Indrapura in Surabaya for the period February - August 2021, 575 patients were found to have comorbid hypertension. The majority of COVID-19 patients with comorbid hypertension are male in the age range of 41-50 and the clinical degree is mild and suffers from clinical symptoms such as coughing. Keywords: COVID-19, Hypertension, Profile.  ABSTRAK Coronavirus Disease 2019 (COVID-19) merupakan jenis penyakit yang disebabkan oleh severe acute respiratory syndrome coronavirus (SARS-CoV-2). Hipertensi menjadi salah satu komorbid yang dapat memperparah pasien COVID-19.  Penelitian ini bertujuan untuk mengetahui profil penderita COVID-19 dengan hipertensi sehingga bermanfaat untuk menentukan tatalaksana yang tepat bagi pasien. Studi retrospektif dilakukan untuk mengkaji rekam medis pasien COVID-19 dengan hipertensi yang dirawat di RS Lapangan Indrapura Surabaya selama Februari – Agustus 2021.Dari 3997 pasien COVID-19 yang dirawat di RS Lapangan Indrapura Surabaya ditemukan 575 pasien dengan komorbid hipertensi (14,39%). Dua ratus dua puluh tiga (38,8%) adalah pasien wanita dan 352 (61,2%) adalah pasien laki-laki. Usia rata-rata adalah 47,2 tahun. Sebagian besar pasien (209, 36,3%) termasuk dalam usia 41-50. Status gizi paling banyak pada pasien adalah obesitas I yaitu 225 pasien (39,1%) dan 361 pasien (62,8%) bekerja sebagai wiraswasta. Pasien COVID-19 dengan hipertensi yang tergolong ringan sebanyak 394 (68,5%) dan seluruh pasien COVID-19 dengan hipertensi, sebanyak 540 (93,3%) sembuh. Gejala klinis paling banyak ditemukan adalah batuk yaitu 248 pasien (43,1%) dan vitamin merupakan terapi simptomatik yang paling banyak diberikan kepada 572 pasien (99,5%). Hipertensi tipe I paling banyak ditemukan pada pasien, yaitu 258 pasien (44,9%) dan sebanyak 426 pasien mendapatkan terapi yaitu monoterapi (74,1%). Komorbid lain yang ditemukan paling banyak pada pasien COVID-19 dengan hipertensi adalah diabetes (48, 8,3%). Dari 3997 pasien COVID-19 yang dirawat di RS Lapangan Indrapura Surabaya periode Februari - Agustus 2021  ditemukan 575 pasien dengan komorbid hipertensi. Mayoritas pasien COVID-19 dengan komorbid hipertensi berjenis kelamin laki-laki dalam rentang usia 41-50 dan derajat klinis ringan serta menderita gejala klinis berupa batuk. Kata Kunci: COVID-19, Hipertensi, Profil